Social workers’ views and experiences of self-care practices: a qualitative interview study - Jian, Miao; Mccusker, Pearse; Mitchell, Mary; Roesch-Marsh, Autumn; Rose, Sarah; Petrova, Lora (Frontiers in Public Health, 2025)
Self-care is increasingly advocated as necessary for improving social workers’ wellbeing. However, it remains a contested term, with limited understanding of social workers’ views and experiences of what it constitutes in practice. This qualitative study employed semi-structured interviews with nine social workers from three local authorities in Scotland. Informed by vulnerability theory, a six-phase thematic analysis was applied to explore social workers’ views and experiences of self-care practices. Three key themes emerged: (1) understanding and conceptualizing self-care, illustrating practitioners’ perceptions of self-care as individualized, multifaceted strategies aimed at both personal wellbeing and professional efficacy, with heightened awareness since COVID-19; (2) the implementation paradox, highlighting fundamental tensions between acknowledging professional vulnerability and managing organizational demands, workload pressures, and insufficient institutional support; and (3) toward sustainable self-care practice, identifying pathways through deliberate individual practices, organizational support, educational preparation, and culturally-sensitive policies. Public health policymakers and healthcare organizations should prioritize structural reforms to enhance workforce resilience, thereby improving service quality, practitioner wellbeing, and overall public health outcomes.